Two new cavernicolous Pselaphinae (Coleoptera: Staphylinidae) from southern China - Yin, Zi-Wei; Zhou, Gu-Chun (Zootaxa, 2018)
Two new cavernicolous pselaphines, Araneibatrus curvitibialis Yin and Zhou, sp. n. and Tribasodites biyun Yin and Zhou, sp. n., are described from southern China, with diagnostic characters illustrated. Both new species can be readily distinguished from their respective congeners by the male dimorphic features on the antennae, legs, and (or) metaventrite, as well as by the configurations of the aedeagi.